(untitled) (Academia Science Repository, 2023)
Pneumonia is the most common complication of alcohol use. In an experiment on animal models, it was found that excessive consumption of ethanol leads to dysfunction of the mucociliary apparatus, which is the cause of the chronic respiratory system, that is, the cleansing of the lower respiratory tract. The function of alveolar macrophages is also impaired.